Stigma and discrimination - An integrative perspective.: Spatial disparities and their impact on the introduction of an antiretroviral therapy scheme for HIV and AIDS treatment in Botswana - Geiselhart, Klaus (ERDKUNDE, 2010)
The article outlines the empirical finding that there are spatial differences in HIV and AIDS-related stigma in Botswana. Most common theories on stigma and discrimination disregard such disparities. It was necessary to develop an integrative perspective in order to explain these findings and this required a broad interdisciplinary review of the literature in the fields of sociology, education, psychology, social psychology and applied sciences. The article explains how stigma and discrimination developed dependent on the local condition of the research sites. The relevance of the topic is apparent from the fact that stigma and discrimination in an urban community hindered the introduction of a medication scheme with antiretroviral drugs.